Sporogenesis in Physcomitrium patens: Intergenerational collaboration and the development of the spore wall and aperture - Renzaglia, Karen S.; Ashton, Neil W.; Suh, Dae-Yeon (Frontiers in Cell and Developmental Biology, 2023)
Although the evolution of spores was critical to the diversification of plants on land, sporogenesis is incompletely characterized for model plants such as Physcomitrium patens. In this study, the complete process of P. patens sporogenesis is detailed from capsule expansion to mature spore, with emphasis on the construction of the complex spore wall and proximal aperture. Both diploid (sporophytic) and haploid (spores) cells contribute to the development and maturation of spores. During capsule expansion, diploid cells of the capsule including spore mother cells (SMCs), inner capsule wall layer (spore sac) and columella contribute a locular fibrillar matrix that contains the machinery and nutrients for spore ontogeny. Nascent spores are enclosed in a second matrix that is surrounded by a thin SMC wall, and suspended in the locular material. As they expand and separate, a band of exine is produced external to a thin foundation layer of tripartite lamellae. Dense globules assemble evenly throughout the locule and these are incorporated onto the spore surface progressively to form the perine external to the exine. On the distal spore surface, the intine forms internally while the spiny perine ornamentation is assembled. The exine is at least partially extrasporal in origin, while the perine is derived exclusively from outside the spore. Across the proximal surface of the polar spores, an aperture begins formation at the onset of spore development and consists of expanded intine, an annulus, and a central pad with radiating fibers. This complex aperture is elastic and enables the proximal spore surface to cycle between being compressed (concave), and expanded (rounded). In addition to providing a site for water intake and germination, the elastic aperture is likely involved in desiccation tolerance. Based on current phylogenies, the ancestral plant spore contained an aperture, exine, intine, and perine. Reductive evolution of liverwort and hornwort spores entailed loss of perine in both groups and the aperture in liverworts. This research serves as the foundation for comparisons with other plant groups and for future studies of the developmental genetics and evolution of spores across plants.